Trusting suppliers from different cultures: an empirical study of Indian customers. (2nd August 2019) - Sharma, Neeru
The purpose of this paper is to investigate if how and to what extent Indian customer firms' trust varies according to where their supplier is based - Europe, North America or Australasia. Further, the paper investigates how trust varies in new and ongoing international trading relationships. A two component trust measure was conceptualised and assessed using confirmatory factor analysis. Test of analysis of variance was used to examine whether trust is different in culturally diverse supplier relationships. Structural path modelling was used to examine links of the two components of trust to relationship commitment and cooperativeness. The analyses reveal that the Indian partner's trust manifests consistently across culturally diverse business relationships. However, the role of trust varies by the age of the business relationship. This paper not only extends the domain of trust in international contexts, but is also an important step to broadening our understanding of business-to-business relationships across cultural borders.